Innovation of Interactive Tests in Maharah Kitabah in Class VIII Arabic Textbooks - Nurazim, Okitra Asri; Baroroh, R Umi (Al-Lisan: Jurnal Bahasa, 2024)
The form of tests or evaluations applied by teachers or educators in various educational institutions until now is still considered less interesting and tends to be monotonous so there is no intense interaction between educators and students in the evaluation process carried out. Often, students feel bored with ordinary tests or text forms that are rigid and monotonous, so there needs to be an update in the model or form of tests that are interactive, innovative, fun, and not boring for students. The purpose of this study is to find out various kinds of interactive Arabic test or quiz models that can be used in learning Arabic so that learning becomes more interesting and fun. This study uses literature research with a qualitative descriptive approach. Secondary data is used as a data source, with data collection techniques in the form of documentation. The result of this research is that there are various forms or models of interactive tests that can be utilized by teachers or Arabic instructors, either by developing their own using several computer-based applications or by utilizing website-based test or quiz applications that already exist on the Internet, where some of these applications can be accessed for free. These findings contribute to the current discussion about appropriate language assessment approaches.